2017
DOI: 10.19080/adoh.2017.05.5555665
|View full text |Cite
|
Sign up to set email alerts
|

Willingness of Parents to Pay for Space Maintainer Therapy for their Children

Abstract: Background and Objective: Space maintainers are the most commonly used tools of interceptive orthodontics. Since their benefit is not immediately visible to the parents there is the possibility that they would not be willing to pay for interceptive care.Methodology: 155 families of children who had lost a primary tooth prematurely participated in the study. A short description of the potential benefits of space-maintainers, parents were asked if they are willing to pay the median cost, Parents who are unwillin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…More opportunities may have arisen to undertake participant face-to-face active communication interviews accompanied by more detailed information regarding the desired service(s). Some studies elicited parental WTP for paediatric services [26,34,36,37,46,52,53]. It is worth mentioning that these case results cannot be indicative of patient (child) perceptions, feelings and utilization of services which is an important aspect of the WTP method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More opportunities may have arisen to undertake participant face-to-face active communication interviews accompanied by more detailed information regarding the desired service(s). Some studies elicited parental WTP for paediatric services [26,34,36,37,46,52,53]. It is worth mentioning that these case results cannot be indicative of patient (child) perceptions, feelings and utilization of services which is an important aspect of the WTP method.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-two studies had response rates of more than 70% and 21 reported no rates of participation. Seven studies elicited WTP of parents for paediatric service without taking into consideration children preferences [26,34,36,37,46,52,53]. Data gathering was done by either an interview (28 studies) or a questionnaire (22 studies).…”
Section: Overview Of the Methodological Aspects Of Wtp Studies In Oramentioning
confidence: 99%
“…However, despite efforts to retain primary teeth, premature loss of tooth or extraction can be unavoidable due to extensive carious lesions and other reasons (Setia et al, 2013). The safest way to maintain space in the arch and prevent malocclusion is by placement of a space maintainer (Mubaraki et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Space maintainers are the most commonly used appliance for interceptive orthodontics (Mubaraki et al, 2017). They are indicated to maintain mesiodistal relationship in the arch (Giorgio, 1973;Terlaje and Donly, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation